Marling a Regosol of Central Java and its Effect on Maize Crop Performance - Kertonegoro, Babang Djadmo (2000)
In this study, a sandy soil (Regosol) derived from volcanic debris is amended with clay soils (Latosol and Grumusol) taken from different localities, with the objective of increasing the productivity of the Regosol as a marginal land. Soil samples taken :from the top 30 em of the soil surfuce are dried, ground, and passed through a sieve with 2.0 mm openings. The Regosol is then thoroughly mixed with the Latosol or Grumusol based on oven weight percentage of 0010, 10%, 20%, 30%, 40% ,50%, and 100% of the Latosol or GrumusoL Mineralogical analyses indicate that the sandy soil (Regosol) is mainly dominated by feldspars and cristobalite while the clay Latosol contains mainly 1:1 type clay minerals of the kaolinite type and most probably layers of halloysite, metahalloysite or kaolinite, with some crlstobalite in it. The Grumusol, on the other hand, is dominated by open 2:1 clay minerals (swelling clay, smectite) mixed with 1:1 type such as halloysite, metahalloysite or kaolinite. The addition of clay soils to the sandy soil changes the textural class towards clay. The particle density and the bulk density of the soil mixture decrease. The total porosity increases. The oxygen diffusion rate (ODR) in the soil mixture is influenced by the water content. Most of the ODR curves are lifted sharply when the matric potential decreases below - 2 kPa. The saturated hydraulic conductivity declines significantly after the addition of 10% to 20% of clay soils. Mixtures containing more than 40% clay soil show similar patterns as those of the original clay soils, while those containing less than 40% clay soil show intermediate behaviour between the sandy soil and the clay soils. The addition of 30% of clay soil causes a substantial reduction in the rate and maximum height of capillary rise during a ten hour period of observation. With increasing amounts of clay soils added, the Atterberg limits, namely the liquid limit (LL), sticky point (SP), and plastic limit (PL), generally increase with increasing amounts of clay soils added. The mechanical resistance declines when the condition is moist. When dry, Grumusol increases mechanical resistance substantially. The aggregate stability tends to decrease, even though there is a tendency for the number of aggregates each with a diameter bigger than 2.0 mm to increase. The response of the soil mixture to the Proctor standard compaction shows that 10% to 40% mixture of Latosol or 10% to 50% of Grumusol brings about an increase in dry soil bulk density. The maximum dry bulk density values of the mixtures are achieved at different critical moisture contents.